Soft contact lens with coating

By forming oxazoline groups and carboxyl/phenol hydroxyl double-layer coatings on soft contact lenses, the problem of insufficient hydrophilicity and lubricity after long-term wear is solved, and higher wearing comfort and economy are achieved .

CN119317865APending Publication Date: 2025-01-14NOF CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380043965.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-02
Filing Date
2023-05-31
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing soft contact lenses have insufficient hydrophilicity and lubricity on the surface after long-term wear, resulting in discomfort in wearing, and some of them are complex in technology and high in economic costs, or poor durability.

Method used

Using soft contact lenses including hydrogel, a first coating with oxazoline groups and a second coating with carboxy or phenolic hydroxyl groups, a double coating is formed by covalent bonding to ensure surface hydrophilicity. and lubricity.

Benefits of technology

Even after a prolonged period of wearing, the surface of the soft contact lens remains sufficiently hydrophilic and lubricating, improving wear comfort and reducing manufacturing and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

There is provided a soft contact lens comprising: a hydrogel; a first coating having an oxazoline group or a first coating having an oxazoline group and a fatty acid that has been covalently bonded to the oxazoline group; and a second coating layer having a carboxyl group or a phenolic hydroxyl group, so that two coating layers are formed on the surface, and the surface has sufficient hydrophilicity and lubricity even if the soft contact lens is continuously worn for a long period of time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a soft contact lens including a coating having excellent surface hydrophilicity and lubricity and a method for manufacturing the lens. Background Art

[0002] It is reported that the number of wearers of soft contact lenses is rapidly increasing due to the ease of use and convenience of soft contact lenses, and the time of wearing soft contact lenses is increasing due to the ease of use and convenience, especially among young people (Non-Patent Document 1). Problems caused by the increase in the time of wearing soft contact lenses are insufficient oxygen to the wearer's cornea due to wearing soft contact lenses, and discomfort caused by wearing.

[0003] Since silicone hydrogel soft contact lenses allow sufficient oxygen to penetrate the cornea, they can minimize adverse effects on corneal health. However, due to their hydrophobicity, wearers will experience dryness, discomfort, etc., so hydrophilization of the contact lens surface is essential.

[0004] As a method of hydrophilization, Patent Documents 1 and 2 disclose "a technology for imparting and enhancing hydrophilicity to the surface of a soft contact lens and improving wearing comfort by mixing polyethylene glycol, a cellulose polymer, etc. in a soft contact lens treatment liquid."

[0005] Patent Document 3 discloses "a technology for improving wearing comfort by adding a copolymer of a phosphorylcholine group-containing monomer and butyl methacrylate, which is known to have a phospholipid-like structure derived from a biological membrane and has extremely high hydrophilicity and moisturizing effect, to a treatment solution for a soft contact lens."

[0006] Among these methods, although excellent hydrophilicity can be imparted to soft contact lenses, since adsorption is achieved on the surface of the contact lens only by physical interaction, there is a concern that the hydrophilicity may become insufficient when the contact lens is worn all day.

[0007] Patent Document 4 discloses “a technique for plasma processing soft contact lenses”.

[0008] Patent Document 5 discloses “a technique for hydrophilizing the surface of a soft contact lens by chemically bonding a soft contact lens having a reactive group and a hydrophilic polymer having a reactive group”.

[0009] Among these methods, by treating the soft contact lens itself, it is possible to impart sufficient hydrophilicity to the surface of the soft contact lens even when the soft contact lens is worn all day.

[0010] Prior art documents

[0011] Non-patent literature

[0012] Non-patent document 1: Walline JJ, 2013, Long-term Contact Lens Wear of Children and Teens, Eye & Contact Lens, 39, 283-289.

[0013] Patent Literature

[0014] Patent Document 1: WO2009 / 032122

[0015] Patent Document 2: WO2012 / 098653

[0016] Patent document 3: US2009 / 0100801

[0017] Patent Document 4: WO2010 / 092686

[0018] Patent Document 5: WO2001 / 074932 Summary of the invention

[0019] Problems to be solved by the present invention

[0020] In the method disclosed in Patent Document 4, since the surface treatment step is complicated, highly managed manufacturing equipment is required, which is also economically disadvantageous. In the method disclosed in Patent Document 5, the durability of the coating is not evaluated, and there is a concern that the hydrophilicity becomes insufficient when the soft contact lens is continuously worn for a long time.

[0021] An object of the present invention is to provide a soft contact lens in which two coating layers are formed on the surface and the surface of the soft contact lens has sufficient hydrophilicity and lubricity even when the soft contact lens is continuously worn for a long period of time.

[0022] Solutions to the problem

[0023] As a result of intensive research, the present inventors have found that a soft contact lens comprising a hydrogel, a first coating having an oxazoline group or a first coating having an oxazoline group and a fatty acid covalently bonded to the oxazoline group, and a second coating having a carboxyl group or a phenolic hydroxyl group can solve the above-mentioned problems, and have completed the present invention.

[0024] That is, the present invention is as follows.

[0025] 1. A soft contact lens, comprising the following (1), (2) and (3), or (1'), (2') and (3'):

[0026] (1) a hydrogel (P1), wherein the hydrogel (P1) has a carboxyl group and / or a phenolic hydroxyl group,

[0027] (2) a first coating layer having oxazoline groups formed on the surface of the hydrogel, the first coating layer comprising a first polymer (P2) comprising a constituent unit derived from an oxazoline group-containing monomer, and

[0028] (3) A second coating layer having carboxyl groups and / or phenolic hydroxyl groups formed on the surface of the first coating layer, the second coating layer comprising: a second polymer (P3) comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate, and constituent units derived from carboxyl group-containing monomers and / or constituent units derived from phenolic hydroxyl group-containing monomers; or a second polymer (P3) comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate and polymerized in the presence of a chain transfer agent containing carboxyl groups and / or phenolic hydroxyl groups or an initiator containing carboxyl groups and / or phenolic hydroxyl groups, wherein

[0029] The carboxyl groups and / or phenolic hydroxyl groups of the hydrogel are bonded to the oxazoline groups of the first coating layer via covalent bonds, and the oxazoline groups of the first coating layer are bonded to the carboxyl groups and / or phenolic hydroxyl groups of the second coating layer via covalent bonds,

[0030] or

[0031] (1') hydrogel (P1'),

[0032] (2') a first coating layer having oxazoline groups formed on the surface of the hydrogel and fatty acids covalently bonded to the oxazoline groups, the first coating layer comprising a first polymer (P2'), the first polymer (P2') comprising a constituent unit derived from a monomer containing an oxazoline group and the first polymer (P2') having bonded thereto the fatty acid covalently bonded to the oxazoline group, and

[0033] (3′) a second coating layer having carboxyl groups and / or phenolic hydroxyl groups formed on the surface of the first coating layer, the second coating layer comprising: a second polymer (P3) comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate, and constituent units derived from carboxyl group-containing monomers and / or constituent units derived from phenolic hydroxyl group-containing monomers; or a second polymer (P3) comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate and being polymerized in the presence of a chain transfer agent containing carboxyl groups and / or phenolic hydroxyl groups or an initiator containing carboxyl groups and / or phenolic hydroxyl groups, wherein:

[0034] The hydrogel is bonded to the first coating layer by introducing fatty acids, and the oxazoline groups of the first coating layer are bonded to the carboxyl groups and / or phenolic hydroxyl groups of the second coating layer via covalent bonds.

[0035] 2. The soft contact lens according to 1, wherein:

[0036] The hydrogel (P1) or (P1′) comprises: a constituent unit derived from (meth)acrylic acid or poly(meth)acrylic acid; and / or a constituent unit derived from hydroxyphenyl (meth)acrylate.

[0037] 3. The soft contact lens according to 1, wherein:

[0038] The fatty acid may be one or more selected from saturated fatty acids having 6 to 30 carbon atoms and unsaturated fatty acids having 6 to 30 carbon atoms.

[0039] 4. The soft contact lens according to any one of 1 to 3, wherein:

[0040] The first coating layer includes a first polymer (P2) or (P2′) comprising a constituent unit derived from 2-isopropenyl-2-oxazoline.

[0041] 5. The soft contact lens according to any one of 1 to 3, wherein:

[0042] The second coating layer comprises a second polymer (P3) comprising a constituent unit derived from (meth)acrylic acid and / or a constituent unit derived from hydroxyphenyl (meth)acrylate.

[0043] 6. The soft contact lens according to any one of 1 to 3, wherein:

[0044] The second coating layer includes a second polymer (P3) comprising a constituent unit derived from 2-methacryloyloxyethyl phosphorylcholine.

[0045] 7. A method for producing a soft contact lens according to any one of 1 to 3, the method comprising the following steps:

[0046] (1) a step of immersing the hydrogel (P1) having carboxyl groups and / or phenolic hydroxyl groups in a solution in which a first polymer (P2) having an oxazoline group is dissolved; and

[0047] (2) A step of immersing the hydrogel having the first coating layer formed thereon after the immersion in step (1) in a solution in which a second polymer (P3) having a carboxyl group and / or a phenolic hydroxyl group is dissolved.

[0048] 8. A method for producing a soft contact lens according to any one of 1 to 3, the method comprising the following steps:

[0049] (1) immersing the hydrogel (P1) in a solution in which a first polymer (P2′) is dissolved, wherein the first polymer (P2′) has an oxazoline group and a fatty acid covalently bonded to the oxazoline group; and

[0050] (2) A step of immersing the hydrogel having the first coating layer formed thereon after the immersion in step (1) in a solution in which a second polymer (P3) having a carboxyl group and / or a phenolic hydroxyl group is dissolved.

[0051] Effects of the Invention

[0052] The surface of the soft contact lens according to the present invention has sufficient hydrophilicity and lubricity even in the case where the soft contact lens is worn continuously for a long period of time. DETAILED DESCRIPTION

[0053] (Soft contact lens and method for manufacturing the same)

[0054] The present invention relates to a soft contact lens comprising the following (1), (2) and (3) or (1'), (2') and (3') and a method for manufacturing the lens.

[0055] (1) a hydrogel (P1) having a carboxyl group and / or a phenolic hydroxyl group,

[0056] (2) a first coating layer having oxazoline groups formed on the surface of the hydrogel, the first coating layer comprising a first polymer (P2), the first polymer (P2) comprising a constituent unit derived from a monomer containing an oxazoline group, and

[0057] (3) A second coating layer having carboxyl groups and / or phenolic hydroxyl groups formed on the surface of the first coating layer, the second coating layer comprising: a second polymer (P3) comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate, and constituent units derived from carboxyl group-containing monomers and / or constituent units derived from phenolic hydroxyl group-containing monomers; or a second polymer (P3) comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate and polymerized in the presence of a chain transfer agent containing carboxyl groups and / or phenolic hydroxyl groups or an initiator containing carboxyl groups and / or phenolic hydroxyl groups, wherein:

[0058] The carboxyl groups and / or phenolic hydroxyl groups of the hydrogel are bonded to the oxazoline groups of the first coating via covalent bonds, and the oxazoline groups of the first coating are bonded to the carboxyl groups and / or phenolic hydroxyl groups of the second coating via covalent bonds,

[0059] or

[0060] (1') hydrogel (P1'),

[0061] (2') a first coating layer having oxazoline groups formed on the surface of the hydrogel and fatty acids covalently bonded to the oxazoline groups, the first coating layer comprising a first polymer (P2'), the first polymer (P2') comprising a constituent unit derived from a monomer containing an oxazoline group and bonded to the fatty acid covalently bonded to the oxazoline group, and

[0062] (3′) a second coating layer having carboxyl groups and / or phenolic hydroxyl groups formed on the surface of the first coating layer, the second coating layer comprising: a second polymer (P3) comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate, and constituent units derived from carboxyl group-containing monomers and / or constituent units derived from phenolic hydroxyl group-containing monomers; or a second polymer (P3) comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate and polymerized in the presence of a chain transfer agent containing carboxyl groups and / or phenolic hydroxyl groups or an initiator containing carboxyl groups and / or phenolic hydroxyl groups, wherein:

[0063] The hydrogel is bonded to the first coating layer by introducing the fatty acid, and the oxazoline groups of the first coating layer are bonded to the carboxyl groups and / or phenolic hydroxyl groups of the second coating layer via covalent bonds.

[0064] In this specification, when describing a preferred numerical range (e.g., concentration range) in stages, each lower limit value and upper limit value can be combined independently. For example, in the description of "preferably 10 or more, more preferably 20 or more, and preferably 100 or less, more preferably 90 or less", "preferable lower limit value: 10" and "preferable upper limit value: 90" can be combined as "10 or more and 90 or less". In addition, for example, the description of "preferably 10 to 100, more preferably 20 to 90" can also be combined as "10 to 90" in the same way.

[0065] In the present specification, "(meth)acrylate" means "acrylate or methacrylate", and the same applies to other similar terms.

[0066] [About hydrogel]

[0067] The hydrogel (P1) of the present invention can be obtained by 1) polymerizing a hydrogel monomer composition in which a compound (1) having a carboxyl group and / or a phenolic hydroxyl group is mixed with one or more monomers, and hydrating the obtained hydrogel polymer.

[0068] The hydrogel (P1') of the present invention is obtained by polymerizing a hydrogel monomer composition not containing the compound (1) and hydrating the obtained hydrogel polymer.

[0069] The hydrogel of the present invention comprises constitutional units derived from various monomers, the constitutional units being based on various monomers or derived from various monomers.

[0070] Examples of monomers include hydrophilic monomers, hydrophobic monomers, silicone-containing monomers, crosslinking agents, UV absorbing vinyl monomers, and the like.

[0071] Examples of the compound (1) having a carboxyl group include monomers such as N,N-2-acrylamidoglycolic acid, β-methyl-acrylic acid (crotonic acid), β-acryloxypropionic acid, sorbic acid, angelic acid, cinnamic acid, 1-carboxy-4-phenyl-1,3-butadiene, itaconic acid, citraconic acid, mesoaconitic acid, glutaric acid, aconitic acid, maleic acid, fumaric acid, (meth)acrylic acid, 2-(meth)acryloyloxyethylsuccinic acid, 2-(meth)acryloyloxyethylhexahydrophthalic acid, 2-(meth)acryloyloxyethyl-phthalic acid, and vinylbenzoic acid; and polymers such as poly(meth)acrylic acid, alginic acid, xanthan gum, gellan gum, gum arabic, pectin, carrageenan, karaya gum, succinoglycan, hyaluronic acid, and chondroitin sulfate.

[0072] One or two or more of these compounds may be used, and (meth)acrylic acid, poly(meth)acrylic acid, alginic acid, and hyaluronic acid are preferred.

[0073] The content of the compound (A) having a carboxyl group is usually 0.1% by mass to 20% by mass, and preferably 0.5% by mass to 10% by mass, relative to 100% by mass of the monomer composition constituting the hydrogel.

[0074] Examples of the compound (1) having a phenolic hydroxyl group include monomers such as hydroxyphenyl (meth)acrylate (4-hydroxyphenyl methacrylate), N-(4-hydroxyphenyl)methacrylamide, and 4-hydroxyphenylmaleimide, and polyphenols such as catechol, anthocyanidin, proanthocyanidin, tannin, rutin, isoflavone, oleuropein, lignin, and curcumin.

[0075] One or two or more of these compounds may be used, and 4-hydroxyphenyl methacrylate and tannin are preferred.

[0076] The content of the compound (A) having a phenolic hydroxyl group is usually 0.1% by mass to 20% by mass, and preferably 1% by mass to 10% by mass, relative to 100% by mass of the monomer composition constituting the hydrogel.

[0077] Examples of hydrophilic monomers include: hydroxyl-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and glycerol (meth)acrylate; ionic group-containing monomers such as styrenesulfonic acid, (meth)acryloyloxyphosphonic acid, and 2-hydroxy-3-(meth)acryloxypropyltrimethylammonium chloride; nitrogen-containing monomers such as (meth)acrylamide, aminoethyl (meth)acrylate, N,N-dimethyl(meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, N-acryloylmorpholine, 2-methacryloyloxyethylphosphocholine, N-vinylpyrrolidone, N-vinylacetamide, and N-methyl-N-vinylacetamide; polyethylene glycol (meth)acrylate; and glycidyl (meth)acrylate.

[0078] As the hydrophilic monomer, one or more of the above can be used. The content of the hydrophilic monomer is usually 10% to 99.9% by mass, preferably 20% to 99% by mass, and more preferably 30% to 98% by mass, relative to 100% by mass of the monomer composition constituting the hydrogel.

[0079] Examples of hydrophobic monomers include linear or branched alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate; aromatic (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate; hydrophobic polyalkylene (meth)acrylates such as polypropylene glycol (meth)acrylate; and styrene monomers such as styrene, methylstyrene, and chloromethylstyrene.

[0080] As the hydrophobic monomer, one or two or more of the above-mentioned monomers may be used.

[0081] The content of the hydrophobic monomer is usually 1% by mass to 20% by mass, and preferably 5% by mass to 10% by mass, relative to 100% by mass of the monomer composition constituting the hydrogel.

[0082] Examples of silicon-containing monomers include tris(trimethylsiloxy)silylpropyl methacrylate, 2-hydroxy-3-[3-[methylbis(trimethylsiloxy)silyl]propoxy]propyl methacrylate, 2-(methacryloyloxy)ethyl=3-[tris(trimethylsiloxy)silyl]propyl=succinate, (meth)acrylate polydimethylsiloxane, and methylbis(trimethylsiloxy)silylpropylglycerol methacrylate. As the silicon-containing monomer, one or two or more of the above may be used.

[0083] The content of the silicon-containing monomer is generally 20 to 90 mass %, preferably 25 to 80 mass %, and more preferably 30 to 70 mass % relative to 100 mass % of the monomer composition constituting the hydrogel.

[0084] Examples of the crosslinking agent (monomer) include tetraethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, tetraethylene glycol divinyl ether, triethylene glycol divinyl ether, diethylene glycol divinyl ether, ethylene glycol divinyl ether, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, bisphenol A dimethacrylate, vinyl methacrylate, ethylenediamine di(meth)acrylamide, glycerol dimethacrylate, triallyl isocyanurate, triallyl cyanurate, allyl (meth)acrylate, N-allyl (meth)acrylamide, 1,3-bis(methacrylamidopropyl)-1,1,3,3-tetrakis(trimethylsiloxy)disiloxane, N,N'-methylenebis(meth)acrylamide, N,N'-ethylenebis(meth)acrylamide, and N,N'-dihydroxyethylenebis(meth)acrylamide.

[0085] As the crosslinking agent, one or two or more of these compounds may be used, and tetraethylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, glycerol dimethacrylate or triethylene glycol divinyl ether is preferred.

[0086] The content of the crosslinking agent is usually 0.01% by mass to 10% by mass, preferably 0.1% by mass to 10% by mass, and more preferably 0.2% by mass to 5% by mass relative to 100% by mass of the monomer composition constituting the hydrogel.

[0087] As monomers other than the above-mentioned monomers, a UV absorbing vinyl monomer may be mixed into the monomer composition for hydrogel.

[0088] Examples of UV absorbing vinyl monomers include 2-(2-hydroxy-5-vinylphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-acryloyloxy)phenyl)-2H-benzotriazole, 2-(2-hydroxy-3-methacrylamidemethyl-5-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methacrylamidephenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-methacrylamidephenyl)-5-methoxybenzotriazole, 2-(2'-hydroxy-5'-methylacrylamidephenyl)-5-methoxybenzotriazole, 2-(2'-hydroxy-5'-methacryloyloxypropylphenyl)benzotriazole, 2-hydroxy-5-methoxy-3-(5-(trifluoromethyl)-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate, 2-hydroxy-5-methoxy-3-(5-methoxy-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate, 3-(5-fluoro-2H-benzo[d][ 1,2,3]triazol-2-yl)-2-hydroxy-5-methoxybenzyl methacrylate, 3-(2H-benzo[d][1,2,3]triazol-2-yl)-2-hydroxy-5-methoxybenzyl methacrylate, 3-(5-chloro-2H-benzo[d][1,2,3]triazol-2-yl]-2-hydroxy-5-methoxybenzyl methacrylate, 2-hydroxy-5-methoxy-3-(5-methyl-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate, 2-Hydroxy-5-methyl-3-(5-(trifluoromethyl)-2H-benzo[d][1,2,3]triazol-2-yl)benzyl methacrylate, 4-allyl-2-(5-chloro-2H-benzo[d][1,2,3]triazol-2-yl)-6-methoxyphenol, 2-{2'-hydroxy-3'-tert-5'[3"-(4"-vinylbenzyloxy)propoxy]phenyl}-5-methoxy-2H-benzotriazole, phenol, 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-vinyl, 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)benzotriazole (2-propenoic acid, 2-methyl-, 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl ester, Norbloc), 2-{2'-hydroxy-3'-tert-butyl-5'-[3'-methacryloyloxypropoxy]phenyl}-5-methoxy-2H-benzotriazole, 2-[2'-hydroxy-3'-tert-butyl-5'-(3'-acryloyloxypropoxy)phenyl] -5-trifluoromethyl-2H-benzotriazole, 2-(2'-hydroxy-5-methylacrylamidephenyl)-5-methoxybenzotriazole, 2-(3-allyl-2-hydroxy-5-methylphenyl)-2H-benzotriazole, 2-(2-hydroxy-3-methylallyl-5-methylphenyl)-2H-benzotriazole, 2-3'-tert-butyl-2'-hydroxy-5'-(3"-dimethylvinylsilylpropoxy)-2'-hydroxy-phenyl)-5-methoxybenzotriazole, 2-(2'-hydroxy-5'-methylacrylamidephenyl)-5-methoxybenzotriazole 2-(3-(tert-butyl)-5-(5-chlorobenzotriazol-2-yl)-4-hydroxyphenyl)-propyl methacrylate (CAS#96478-15-8) and 2-(3-(tert-butyl)-4-hydroxy-5-(5-methoxy-2H-benzo[d][1,2,3]triazol-2-yl)-propyl methacrylate (CAS#96478-15-8) ) phenoxy) ethyl methacrylate; phenol, and 2-(5-chloro-2H-benzotriazol-2-yl)-6-methoxy-4-(2-propen-1-yl) (CAS#12601421-20-5); 2-[2-hydroxy-5-[3-(methacryloyloxy)propyl]-3-tert-butylphenyl]-5-chloro-2H-benzotriazole; phenol, 2-(5-vinyl-2H-benzotriazol-2-yl)-4-methyl-, homopolymer (9CI) (CAS#83063-87-0), etc. ,

[0089] The content of the UV absorbing vinyl monomer is usually 0.1 to 30 parts by mass, preferably 0.2 to 20 parts by mass, and more preferably 0.3 to 10 parts by mass, relative to 100 parts by mass of the monomer composition constituting the hydrogel.

[0090] The monomer composition for hydrogel may further contain a solvent as required. As the solvent, a solvent that does not react under polymerization conditions can be used, and examples thereof include: water, tetrahydrofuran, tripropylene glycol methyl ether, dipropylene glycol methyl ester, ethylene glycol n-butyl ether, acetone, methyl ethyl ketone, diethylene glycol n-butyl ether, diethylene glycol methyl ether, ethylene glycol phenyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, dipropylene glycol methyl ether acetate, propylene glycol n-propyl ether, dipropylene glycol n-propyl ether, tripropylene glycol n-butyl ether, propylene glycol n-butyl ether, dipropylene glycol n-butyl ether, tripropylene glycol n-butyl ether, propylene glycol phenyl ether, dipropylene glycol dimethyl ether, polyethylene glycol, polypropylene glycol, ethyl acetate, butyl acetate, amyl acetate, lactic acid Methyl ester, ethyl lactate, isopropyl lactate, dichloromethane, chloroform, ethanol, 1-propanol, 2-propanol, 2-butanol, menthol, 1-hexanol, cyclohexanol, cyclopentanol, borneol, 2-pentanol, 3-pentanol, 2-hexanol, 3-hexanol, 3-methyl-2-butanol, 2-heptanol, 2-octanol, 2-nonanol, 2-decanol, 3-octanol, norborneol, tert-butyl alcohol, tert-pentanol, 2-methyl-2-pentanol, 2,3-dimethyl-2-butanol, 3-methyl-3-pentanol, 1-methylcyclohexanol, 2-methyl-2-hexanol, 3,7-dimethyl-3-octanol, 1-chloro-2-methyl-2-propanol, 2- methyl-2-heptanol, 2-methyl-2-octanol, 2-methyl-2-nonanol, 2-methyl-2-decanol, 3-methyl-3-hexanol, 3-methyl-3-heptanol, 4-methyl-4-heptanol, 3-methyl-3-octanol, 4-methyl-4-octanol, 3-methyl-3-nonanol, 4-methyl-4-nonanol, 3-methyl-3-octanol, 3-ethyl-3-hexanol, 3-methyl-3-heptanol, 4-ethyl-4-heptanol, 4-propyl-4-heptanol, 4-isopropyl-4-heptanol, 2,4-dimethyl-2-pentanol, 1-methylcyclopentanol, 1-ethylcyclopentanol, 1-ethylcyclopentanol, 3-Hydroxy-3-methyl-1-butene, 4-hydroxy-4-methyl-1-cyclopentanol, 2-phenyl-2-propanol, 2-methoxy-2-methyl-2-propanol, 2,3,4-trimethyl-3-pentanol, 3,7-dimethyl-3-octanol, 2-phenyl-2-butanol, 2-methyl-1-phenyl-2-propanol, 3-ethyl-3-pentanol, 1-ethoxy-2-propanol, 1-methyl-2-propanol, 1-methyl-2-pyrrolidone, N,N-dimethylpropionamide, dimethyl sulfoxide, dimethylformamide, dimethylacetamide and N-methylpyrrolidone, and one or more of the above can be used.

[0091] The polymerization of the monomer composition for hydrogel can be carried out by a conventionally known method. For example, the polymerization can be carried out using a known polymerization initiator such as a thermal polymerization initiator or a photopolymerization initiator.

[0092] Thermal polymerization initiators are known to those skilled in the art, and examples thereof include: azo-based polymerization initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] disulfate dihydrate, 2,2'-azobis(2- 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis(1-imino-1-pyrrolidine-2-methylpropane) dihydrochloride, 2,2'-azobis[2-methyl-N-{1,1-bis(hydroxymethyl)-2-hydroxyethyl}propionamide], 2,2'-azobis[2-methyl-N-{1,1-bis(hydroxymethyl)-2-hydroxyethyl}propionamide], 2,2'-azobis[2-methyl [2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis(2-methylpropionamidine) dihydrochloride, and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide]; and peroxide polymerization initiators such as benzoyl peroxide, tert-butyl hydroperoxide, cumene hydroperoxide, lauroyl peroxide, tert-butyl peroxyhexanoate and 3,5,5-trimethylhexanoyl peroxide, and one or more of the above can be used.

[0093] From the viewpoint of safety and availability, an azo-based polymerization initiator is preferred, and from the viewpoint of reactivity, 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylpropionic acid)dimethyl ester, and 2,2'-azobis(2,4-dimethylvaleronitrile) are particularly preferred.

[0094] Examples of the photopolymerization initiator include acetophenone, benzophenone, 2-benzoylbenzoic acid, 4-benzoylbenzoic acid, methyl 2-benzoylbenzoate, benzoin methyl ether, benzoin ethyl ether, benzoin isobutyl ether, diethoxyacetophenone, 2-isopropoxybenzophenone, 2-ethylanthraquinone, 2,4-diethylthioxanthene-9-one, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, bis-(2,6-dichlorobenzoyl)-4-N-propylphenylphosphine oxide, and bis-(2,6-dichlorobenzoyl)-4-N-butylphenylphosphine oxide, which are Darocur (registered trademark) type and Irgacur (registered trademark) type.

[0095] Preferred are Darocur (registered trademark) 1173, Darocur (registered trademark) 2959, and Irgacur (registered trademark) 819. For example, a reactive photoinitiator capable of incorporating a macromonomer or capable of serving as a special monomer is also preferred.

[0096] The polymer for hydrogel can be obtained by a method known to those skilled in the art, and is produced, for example, by using a mold (gold mold) having a hydrophobic surface made of polypropylene or the like, filling the mold with a monomer composition for hydrogel, and polymerizing the monomer composition.

[0097] The polymerization reaction can be carried out in air, and can be carried out in an inert gas atmosphere such as nitrogen or argon to increase the polymerization rate. In the case of polymerization in an inert gas atmosphere, the pressure in the polymerization system is preferably 1 kgf / cm 2 the following.

[0098] The polymer for hydrogel obtained as described above can be peeled off from the mold by a known method and taken out in a dry state. In addition, the polymer for hydrogel can be immersed in a solvent (e.g., water, methanol, ethanol, 1-propanol, 2-propanol, and a mixed solution thereof) together with the mold to swell the contact lens substrate and peel off.

[0099] In addition, by repeatedly immersing the hydrogel polymer in a solvent for washing, the residues, residues, by-products, etc. of each component can be removed. For example, the polymer can be washed by immersing it in the above alcohol or an aqueous alcohol solution having a concentration of 30% by mass or more at 10°C to 40°C.

[0100] After washing, the polymer for hydrogel may be further washed by immersing it in an aqueous alcohol solution having an alcohol concentration of 20% by mass to 50% by mass for 10 minutes to 5 hours.

[0101] By adding the first polymer during washing, purification and coating of the first layer can also be performed simultaneously.

[0102] The hydrogel of the present invention can be obtained by immersing the polymer for hydrogel in water for 10 minutes to 5 hours after alcohol washing.

[0103] Before water washing, washing may be added by immersing the polymer for hydrogel in an alcohol aqueous solution having an alcohol concentration of 20% to 50% by mass for 10 minutes to 5 hours. The water is preferably pure water such as RO water, ion exchange water, and distilled water.

[0104] [About the first coating]

[0105] There are no particular restrictions on the first polymer (P2) constituting (contained in) the first coating layer, as long as it is a polymer comprising a constituent unit derived from a monomer containing an oxazoline group, or a first polymer (P2') comprising a constituent unit derived from a monomer containing an oxazoline group and bonded to a fatty acid covalently bonded to the oxazoline group.

[0106] The constitutional unit refers to a unit based on each monomer or a compound contained in a polymer derived from each monomer.

[0107] Examples of oxazoline group-containing monomers (oxazoline group-containing compounds) include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline. One or a mixture of two or more selected from the group consisting of these can be used, and 2-isopropenyl-2-oxazoline is preferred.

[0108] The first polymer is preferably a copolymer with other monomers other than the oxazoline group-containing monomer, and examples of the other monomers include methacrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, perfluoroalkylethyl acrylate, phenyl acrylate, 2-hydroxyethyl acrylate, 2-aminoethyl acrylate and its salts, methoxypolyethylene glycol acrylate, monoesters of acrylic acid and polyethylene glycol, methyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, 2-hydroxyethyl methacrylate, methoxypolyethylene glycol methacrylate, monoesters of methacrylic acid and polyethylene glycol, and methacrylic acid. 2-aminoethyl ester and its salt; (meth) acrylates such as sodium (meth) acrylate and ammonium (meth) acrylate; unsaturated nitriles such as (meth) acrylonitrile; unsaturated amides such as (meth) acrylamide, N-hydroxymethyl (meth) acrylamide and N-(2-hydroxyethyl) (meth) acrylamide; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α, β-unsaturated monomers such as vinyl chloride, vinylidene chloride and vinyl fluoride; and α, β-unsaturated aromatic monomers such as styrene, α-methylstyrene and sodium styrene sulfonate. Ethyl acrylate and methoxy polyethylene glycol methacrylate are preferred.

[0109] The first polymer (P2') comprising a constitutional unit derived from an oxazoline group-containing monomer and bonded to a fatty acid covalently bonded to an oxazoline group can be obtained by reacting a polymer having an oxazoline group with a saturated fatty acid having 6 to 30 carbon atoms and an unsaturated fatty acid having 6 to 30 carbon atoms.

[0110] In the reaction example, the oxazoline group forms a covalent bond (amide ester bond) with the carboxyl group of the fatty acid.

[0111] Examples of the saturated fatty acids having 6 to 30 carbon atoms include caproic acid, heptanoic acid, caprylic acid, nonanoic acid, capric acid, lauric acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, arachidic acid, heneicosanoic acid, behenic acid, lignoceric acid, cerotic acid, montanic acid, melissic acid, isocaproic acid, isoheptanoic acid, isooctanoic acid, isononanoic acid, isodecanoic acid, isolauric acid, isomyristic acid, isopentadecanoic acid, isopalmitic acid, isoheptadecanoic acid, isostearic acid, isoarachidic acid, isoheneicosanoic acid, isobehenic acid, isolignoceric acid, isoceric acid, isomontanic acid and isomelissic acid.

[0112] Examples of the unsaturated fatty acid having 6 to 30 carbon atoms include myristoleic acid, palmitoleic acid, hexadecenoic acid, oleic acid, elaidic acid, octadecenoic acid, gadoleic acid, eicosenoic acid, erucic acid, nervonic acid, linoleic acid, eicosadienoic acid, docosadienoic acid, linolenic acid, pinolenic acid, octadecatrienoic acid, melisic acid, eicosatrienoic acid, stearatetraenoic acid, arachidonic acid, eicosatetraenoic acid, adrenic acid, docosapentaenoic acid, eicosapentaenoic acid, osbonic acid, ichthyic acid, tetracosapentaenoic acid, docosahexaenoic acid and nisinic acid, preferably capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, isodecanoic acid, isolauric acid, isomyristic acid, isopalmitic acid, isostearic acid, myristoleic acid, palmitoleic acid, oleic acid, elaidic acid, gadoleic acid, eicosenoic acid, erucic acid and nervonic acid, and more preferably isostearic acid and oleic acid.

[0113] In the above first polymer, the amount of the constituent unit derived from the oxazoline group-containing monomer is preferably 10 mol % to 95 mol %, more preferably 20 mol % to 90 mol %, still more preferably 25 mol % to 80 mol %, relative to 100 mol % of all constituent units.

[0114] The weight average molecular weight of the above-mentioned first polymer is preferably 5,000 to 150,000, and more preferably 10,000 to 100,000.

[0115] As the first polymer, a commercially available polymer may be used, and preferred examples of the commercially available oxazoline group-containing polymer include EPOCROS (registered trademark) WS-300 and EPOCROS (registered trademark) WS-700 manufactured by Nippon Shokubai Co., Ltd.

[0116] [About the second coating]

[0117] There are no particular restrictions on the second polymer (P3) constituting (contained in) the second coating layer, as long as the second polymer (P3) is a polymer comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate, and constituent units derived from carboxyl group-containing monomers and / or constituent units derived from phenolic hydroxyl group-containing monomers; or is a polymer comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate and polymerized in the presence of a chain transfer agent containing carboxyl groups and / or phenolic hydroxyl groups or an initiator containing carboxyl groups and / or phenolic hydroxyl groups.

[0118] The constitutional unit refers to a unit based on each monomer or a compound contained in a polymer derived from each monomer.

[0119] Examples of carboxyl-containing monomers (carboxyl-containing compounds) include β-methyl-acrylic acid (crotonic acid), β-acryloyloxypropionic acid, sorbic acid, angelic acid, cinnamic acid, 1-carboxy-4-phenyl-1,3-butadiene, itaconic acid, citraconic acid, mesoaconitic acid, glutaric acid, aconitic acid, maleic acid, fumaric acid, (meth)acrylic acid, 2-(meth)acryloyloxyethylsuccinic acid, and vinylbenzoic acid. (Meth)acrylic acid is preferred, and methacrylic acid is more preferred.

[0120] The polymer having a carboxyl group includes, as a main component, poly(meth)acrylic acid, alginic acid, xanthan gum, gellan gum, gum arabic, pectin, carrageenan, karaya gum, succinoglycan, hyaluronic acid, chondroitin sulfate, and the like.

[0121] Other polymers having carboxyl groups include polyethylene glycol (PEG) having one carboxyl group at the end (e.g., HO-PEG-COH, H3CO-PEG-COOH), PEG having carboxyl groups at both ends (HOOC-PEG-COOH), multi-arm PEG having more than one carboxyl group, PEG dendrimers, etc., as main components.

[0122] The polymer having a carboxyl group is preferably a copolymer obtained by a polymerization reaction with a hydrophilic monomer other than the monomer having a carboxyl group. Examples of hydrophilic monomers other than monomers having a carboxyl group include hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and glycerol (meth)acrylate; ionic group-containing monomers such as styrenesulfonic acid, (meth)acryloyloxyphosphonic acid, and 2-hydroxy-3-(meth)acryloyloxypropyltrimethylammonium chloride; nitrogen-containing monomers such as (meth)acrylamide, aminoethyl (meth)acrylate, N,N-dimethyl(meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, N-acryloylmorpholine, 2-methacryloyloxyethylphosphocholine, N-vinylpyrrolidone, N-vinylacetamide, and N-methyl-N-vinylacetamide; polyethylene glycol (meth)acrylate; and glycidyl (meth)acrylate.

[0123] As the hydrophilic monomer other than the monomer having a carboxyl group, one or two or more of these examples can be used, and 2-methacryloyloxyethyl phosphorylcholine, N-vinyl pyrrolidone, and polyethylene glycol (meth)acrylate are preferred, and 2-methacryloyloxyethyl phosphorylcholine is more preferred.

[0124] Examples of the phenolic hydroxyl group-containing monomer (phenolic hydroxyl group-containing compound) include hydroxyphenyl (meth)acrylate (4-hydroxyphenyl methacrylate), N-(4-hydroxyphenyl)methacrylamide, and 4-hydroxyphenylmaleimide, and one or more of these examples may be used. Hydroxyphenyl (meth)acrylate (4-hydroxyphenyl methacrylate) is preferred.

[0125] Examples of hydrophilic monomers other than the phenolic hydroxyl group-containing monomers include hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and glycerol (meth)acrylate; ionic group-containing monomers such as styrenesulfonic acid, (meth)acryloyloxyphosphonic acid, and 2-hydroxy-3-(meth)acryloxypropyltrimethylammonium chloride; nitrogen-containing monomers such as (meth)acrylamide, aminoethyl (meth)acrylate, N,N-dimethyl (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, N-acryloylmorpholine, 2-methacryloyloxyethyl phosphorylcholine, N-vinylpyrrolidone, N-vinylacetamide, and N-methyl-N-vinylacetamide; polyethylene glycol (meth)acrylate; and glycidyl (meth)acrylate. As the hydrophilic monomer other than the phenolic hydroxyl group-containing monomer, one or more of the above examples can be used, preferably 2-methacryloyloxyethyl phosphorylcholine, N-vinyl pyrrolidone and polyethylene glycol (meth)acrylate, and more preferably 2-methacryloyloxyethyl phosphorylcholine.

[0126] Examples of the chain transfer agent containing a carboxyl group and / or a phenolic hydroxyl group include 2-(((dodecylthio)carbonylthio)thio)propionic acid, 3-((((1-carboxyethyl)thio)carbonylthio)thio)propionic acid, 4-((((2-carboxyethyl)thio)carbonylthio)thio)-4-cyanopentanoic acid, 4-cyano-4-(((dodecylthio)carbonylthio)thio)pentanoic acid, 2-(dodecylthiocarbonylthiothio)-2-methylpropionic acid, 3-(((benzylthio)carbonylthio)thio)propionic acid, S-(thiobenzoyl)thioglycolic acid, and 4-cyano-4-((phenylcarbonylthio)thio)pentanoic acid.

[0127] Examples of the initiator containing a carboxyl group and / or a phenolic hydroxyl group include iodoacetic acid, 2-iodopropionic acid, 2-iodobutyric acid, and 2-iodo-2-phenylacetic acid.

[0128] The amount of the constituent units derived from the carboxyl group-containing monomer or the phenolic hydroxyl group-containing monomer contained in the above second polymer is preferably 5 mol % to 95 mol %, more preferably 7 mol % to 90 mol %, and further preferably 10 mol % to 80 mol %, relative to 100 mol % of all constituent units.

[0129] The weight average molecular weight of the second polymer is 1,000 to 5,000,000, preferably 10,000 to 3,000,000, more preferably 20,000 to 2,000,000, and further preferably 50,000 to 1,500,000.

[0130] When the weight average molecular weight is less than 1,000, hydrophilicity and lubricity may be insufficient, and when the weight average molecular weight is greater than 5,000,000, viscosity may increase and handling may be difficult.

[0131] [Polymerization reaction]

[0132] The polymerization reaction for obtaining the above-mentioned first polymer (first coating) and the second polymer (second coating) can be carried out by known methods, such as by replacing with an inert gas such as nitrogen, carbon dioxide, argon or helium or in the atmosphere of the inert gas, in the presence of a free radical polymerization initiator, free radical polymerization, such as bulk polymerization, suspension polymerization, emulsion polymerization and solution polymerization. From the perspective of purification, solution polymerization is preferred. The purification of the polymer can be carried out by general purification methods, such as reprecipitation, dialysis or ultrafiltration.

[0133] Examples of the radical polymerization initiator include an azo-based radical polymerization initiator, an organic peroxide, a persulfate, and an iodine-based polymerization initiator.

[0134] Examples of the azo-based radical polymerization initiator include 2,2′-azobis(2-methylpropionamidine) dihydrochloride, 2,2-azobis(2-diaminopropyl) dihydrochloride, 2,2-azobis(2-(5-methyl-2-imidazolin-2-yl)propane) dihydrochloride, 4,4-azobis(4-cyanovaleric acid), 2,2-azobisisobutyramide dihydrate, 2,2-azobis(2,4-dimethylvaleronitrile), and 2,2-azobisisobutyronitrile (AIBN).

[0135] Examples of the organic peroxide include tert-butyl peroxyneodecanoate (Perbutyl (registered trademark) ND), benzoyl peroxide, diisopropyl peroxydicarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, tert-butyl peroxydiisobutyrate, lauroyl peroxide, and succinic acid peroxide (=succinyl peroxide).

[0136] Examples of persulfates include ammonium persulfate, potassium persulfate, and sodium persulfate.

[0137] Examples of the iodine-based polymerization initiator include iodoacetic acid, 2-iodopropionic acid, 2-iodobutyric acid, and 2-iodo-2-phenylacetic acid.

[0138] These radical polymerization initiators may be used alone or in combination of two or more thereof. The amount of the polymerization initiator used is usually 0.001 to 10 parts by mass, and preferably 0.01 to 5.0 parts by mass, relative to 100 parts by mass of the monomer composition of the hydrophilic polymer.

[0139] The polymerization reaction can be carried out in the presence of a chain transfer agent, and examples of the chain transfer agent include 2-(((dodecylthio)carbonylthio)thio)propionic acid, 3-((((1-carboxyethyl)thio)carbonylthio)thio)propionic acid, 4-((((2-carboxyethyl)thio)carbonylthio)thio)-4-cyanopentanoic acid, 4-cyano-4-(((dodecylthio)carbonylthio)thio)pentanoic acid, 2-(dodecylthiocarbonylthiothio)-2-methylpropionic acid, 3-(((benzylthio)carbonylthio)thio)propionic acid, S-(thiobenzoyl)thioglycolic acid, and 4-cyano-4-((phenylcarbonylthio)thio)pentanoic acid.

[0140] The polymerization reaction can be carried out in the presence of a solvent, and as the solvent, a solvent that dissolves the monomer composition and does not participate in the reaction can be used. Examples of the solvent include: water; alcohol solvents such as methanol, ethanol, n-propanol, and isopropanol; ketone solvents such as acetone, methyl ethyl ketone, and diethyl ketone; ester solvents such as ethyl acetate; linear or cyclic ether solvents such as ethyl cellosolve, tetrahydrofuran, and N-methylpyrrolidone; and nitrogen-containing solvents such as acetonitrile and nitromethane. Preferred examples thereof include water or alcohol or a mixed solvent thereof.

[0141] [Method for manufacturing soft contact lens]

[0142] The method for manufacturing the soft contact lens of the present invention is not particularly limited as long as the method includes: a step of bonding the hydrogel and the first polymer to each other via a covalent bond, or by introducing a fatty acid of the first polymer into the hydrogel, thereby bonding the hydrogel and the first coating to each other, and a step of further bonding the first polymer and the second polymer to each other via a covalent bond. For example, the following steps can be exemplified.

[0143] (1) immersing the hydrogel having carboxyl groups and / or phenolic hydroxyl groups in a solution in which a first coating layer having oxazoline groups is dissolved, and

[0144] (2) immersing the hydrogel having the first coating formed thereon after the immersion in step (1) into a solution in which a second coating having carboxyl groups and / or phenolic hydroxyl groups is dissolved,

[0145] or

[0146] (1) immersing the hydrogel in a solution in which a first coating layer having an oxazoline group and a fatty acid covalently bonded to the oxazoline group is dissolved, and

[0147] (2) A step of immersing the hydrogel having the first coating layer formed thereon after the immersion in step (1) in a solution in which a second coating layer having a carboxyl group and / or a phenolic hydroxyl group is dissolved.

[0148] [Reaction between hydrogel and first coating]

[0149] The hydrogel and the first coating (first polymer) are bonded to each other via covalent bonds by reacting the carboxyl group and / or phenolic hydroxyl group of the hydrogel with the oxazoline group in the first polymer.

[0150] Alternatively, the hydrogel and the first coating (first polymer) are bonded to each other by allowing the hydrogel to incorporate fatty acids in the first polymer.

[0151] The above reaction is performed by immersing the hydrogel in a solution in which the first polymer is dissolved at a temperature of about 20° C. to about 90° C. for about 0.2 hours to about 24 hours, preferably about 0.5 hours to about 12 hours, and further preferably about 1 hour to 6 hours.

[0152] The solvent in which the first polymer is dissolved is not particularly limited as long as it is a solvent that dissolves the first polymer and does not participate in the reaction, and is preferably water, methanol, ethanol, 1-propanol, 2-propanol, or a mixed solvent thereof.

[0153] The above reaction may be carried out together with the step of washing the polymer for the hydrogel. For example, the above reaction is carried out by immersing the hydrogel in a washing solution in which the first polymer is dissolved, and washing the hydrogel at a temperature of about 20° C. to about 90° C. for about 0.2 hours to about 24 hours, preferably about 0.5 hours to about 12 hours, and more preferably about 1 hour to 6 hours.

[0154] [Reaction between the first coating and the second coating]

[0155] In the reaction between the first coating layer and the second coating layer, the oxazoline group in the first polymer and the carboxyl group and / or phenolic hydroxyl group in the second polymer are reacted with each other to be bonded via a covalent bond.

[0156] The above reaction is carried out by immersing the hydrogel obtained by reacting with the first polymer in a solution in which the second polymer is dissolved at a temperature of about 20° C. to about 125° C. for about 0.2 hour to about 24 hours, preferably about 0.5 hour to about 12 hours, and further preferably about 1 hour to 6 hours.

[0157] The solvent in which the second polymer is dissolved is not particularly limited as long as it is a solvent that dissolves the second polymer and does not participate in the reaction, and is preferably water, methanol, ethanol, 1-propanol, 2-propanol, or a mixed solvent thereof.

[0158] The above reaction may be carried out together with a washing step of the hydrogel after the reaction with the first polymer. For example, the above reaction is carried out by immersing the hydrogel after the reaction with the first polymer in a washing solution in which the second polymer is dissolved and washing the hydrogel at a temperature of about 20° C. to about 90° C. for about 0.2 hours to about 24 hours, preferably about 0.5 hours to about 12 hours, and more preferably about 1 hour to 6 hours.

[0159] The above reaction can be carried out together with the sterilization step of the hydrogel after the reaction with the first polymer. For example, the hydrogel after the reaction with the first polymer is immersed in a lens package or a sealed vial together with a physiological saline solution in which the second polymer is dissolved. Thereafter, the above reaction is carried out by autoclaving at a temperature of about 118° C. to about 125° C. for about 20 minutes to 90 minutes.

[0160] [Configuration Example of the Soft Contact Lens of the Present Invention]

[0161] Examples of the configuration of the soft contact lens of the present invention include, but are not particularly limited to, the following combinations.

[0162] (1) The hydrogel comprises constituent units derived from 2-hydroxyethyl methacrylate and methacrylic acid, the first coating layer comprises constituent units derived from 2-isopropenyl-2-oxazoline, and the second coating layer comprises constituent units derived from methacrylic acid.

[0163] (2) The hydrogel comprises a constituent unit derived from methacrylic acid, the first coating layer comprises a constituent unit derived from 2-isopropenyl-2-oxazoline, and the second coating layer comprises a constituent unit derived from methacrylic acid.

[0164] (3) The hydrogel comprises a constituent unit derived from 4-hydroxyphenyl methacrylate, the first coating layer comprises a constituent unit derived from 2-isopropenyl-2-oxazoline, and the second coating layer comprises a constituent unit derived from 4-hydroxyphenyl methacrylate.

[0165] (4) The hydrogel comprises polyacrylic acid (preferably having a weight average molecular weight of 5,000 to 1,000,000), the first coating comprises EPOCROS WS-300, and the second coating comprises a constituent unit derived from methacrylic acid.

[0166] (5) The first coating layer comprises EPOCROS WS-300 and oleic acid, and the second coating layer comprises a constituent unit derived from methacrylic acid.

[0167] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.

[0168] The components used in Synthesis Examples, Examples, and Comparative Examples are shown below.

[0169] IPO: 2-isopropenyl-2-oxazoline

[0170] MAA: Methacrylic acid

[0171] PAA: Polyacrylic acid

[0172] 4-HPMA: 4-Hydroxyphenyl Methacrylate

[0173] HEMA: 2-Hydroxyethyl Methacrylate

[0174] HBMA: 2-Hydroxybutyl Methacrylate

[0175] NVP: N-vinyl pyrrolidone

[0176] DMAA: N,N-dimethylacrylamide

[0177] MMA: Methyl Methacrylate

[0178] ETS: 2-(Methacryloyloxy)ethyl=3-[tris(trimethylsiloxy)silyl]propyl=succinate

[0179] SiGMA: Methylbis(trimethylsiloxy)silylpropylglycerol methacrylate

[0180] TRIS: Tris(trimethylsiloxy)silylpropyl methacrylate

[0181] MCR-M11: Polydimethylsiloxane single-end methacrylate with a molecular weight of about 1000

[0182] TEGDMA: Tetraethylene glycol dimethacrylate

[0183] EtOH: ethanol

[0184] NPA: 1-Propanol (n-propanol)

[0185] IPA: 2-Propanol (isopropyl alcohol)

[0186] HeOH: Hexanol

[0187] AIBN: 2,2'-azobis(isobutyronitrile)

[0188] I-819: Irgacur (registered trademark) 819 phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide

[0189] MPC: 2-methacryloyloxyethyl phosphorylcholine

[0190] PME-1000: methoxy polyethylene glycol methacrylate with a molecular weight of about 1000

[0191] EA: Ethyl acrylate

[0192] BMA: Butyl Methacrylate

[0193] PB-ND: tert-Butyl Peroxyneodecanoate

[0194] V-50: 2,2'-Azobis(2-methylpropionamidine) dihydrochloride

[0195] [Adjustment of hydrogel]

[0196] [Synthesis example 1-1]

[0197] 2.0 mass % of MAA, 22.5 mass % of HBMA, 20.0 mass % of NVP, 20.0 mass % of SiGMA, 5.0 mass % of MMA, 30.0 mass % of MCR-M11, 0.50 mass % of TEGDMA, and 10.0 mass parts of NPA were mixed, and then 0.5 mass parts of AIBN was dissolved therein to obtain a composition for hydrogel.

[0198] The composition for hydrogel was dispensed into a mold and heated in a polymerization furnace set at 100° C. for 2 hours to obtain a polymer for hydrogel.

[0199] The polymer was taken out from the mold, immersed in about 20 g of a solution of 2-propanol:ion exchange water = 1:1 for 4 hours, and then immersed in about 20 g of ion exchange water for 2 hours to obtain a hydrogel having a carboxyl group.

[0200] [Synthesis Examples 1-2 to 1-4]

[0201] Except that the mixing ratio of each component in the composition and the polymerization conditions were changed as shown in Table 1, a hydrogel was prepared in the same manner as in Synthesis Example 1-1.

[0202] In Synthesis Example 1-2, the hydrogel composition dispensed into the mold was placed in a UV-LED irradiator (irradiation light wavelength: 405 nm) and irradiated at room temperature at 1.5 mW / cm 2 The polymer was irradiated with UV light at an irradiation intensity of 1000 nm for 30 minutes to obtain a hydrogel.

[0203] The hydrogel of Synthesis Example 1-2 has phenolic hydroxyl groups.

[0204] The hydrogel of Synthesis Example 1-3 has carboxyl groups. The average molecular weight of PAA is 250,000.

[0205] The hydrogel of Synthesis Example 1-4 has no carboxyl group and no phenolic hydroxyl group.

[0206] [Preparation of the first polymer solution]

[0207] [Synthesis example 2-1]

[0208] A polymerization solution was obtained by dissolving 16.3 g of IPO and 3.7 g of EA in 180.0 g of water.

[0209] After the temperature of the polymerization solution was raised to 60°C under a nitrogen atmosphere, 0.50 g of V-50 was added to initiate polymerization, and a copolymer solution was obtained after reacting for 9 hours. After impurities were removed from the obtained polymer solution by dialysis purification, the solution was diluted with water so that the concentration of the first polymer became 5% by mass, thereby obtaining a first polymer aqueous solution.

[0210] The method of measuring the weight average molecular weight of the obtained copolymer is as follows: In addition, the measurement was also performed in the same manner in Synthesis Examples 2-2 to 3-1 to 3-4.

[0211] 1 mg of copolymer was dissolved in 1 g of purified water.

[0212] Column: SB-802.5 HQ + SB-806MN HQ

[0213] Mobile phase: 20 mM phosphate buffer (pH: 7.0)

[0214] Standard material: Polyethylene glycol / oxide

[0215] Measuring instrument: HLC-8320GPC (manufactured by TOSOH CORPORATION)

[0216] Calculation method of weight average molecular weight: Molecular weight calculation program (EcoSEC data analysis)

[0217] Flow rate: 0.5 mL per minute

[0218] Injection volume: 100 μL

[0219] Column furnace: 45°C

[0220] Measurement time: 70 minutes

[0221] [Synthesis example 2-2]

[0222] A polymerization solution was obtained by dissolving 4.0 g of IPO, 15.1 g of PME-1000 and 0.9 g of EA in 180.0 g of water. After the temperature of the polymerization solution was raised to 60° C. under a nitrogen atmosphere, 0.50 g of V-50 was added to initiate polymerization, and a copolymer solution was obtained after reacting for 9 hours. After removing impurities from the obtained polymer solution by dialysis purification, the solution was diluted with water so that the concentration of the first polymer became 5% by mass, thereby obtaining a first polymer aqueous solution.

[0223] [Synthesis example 2-3]

[0224] 5.0 g of IPA and 0.2 g of oleic acid were added to 5.0 g of EPOCROS (registered trademark) WS-300 and heated at 60°C for 12 hours to allow the oleic acid portion to bind to the oxazoline group of EPOCROS (registered trademark) WS-300. Thereafter, 2.0 g of an adsorbent was added to the reaction solution, and the mixture was stirred at room temperature for 2 hours to remove unreacted oleic acid. The adsorbent was removed by filtration to obtain a purified reaction solution. The purified reaction solution was concentrated to obtain a first polymer solution having an oxazoline group and oleic acid bound to the oxazoline group.

[0225] [Synthesis example 2-4]

[0226] A commercially available polymer can also be used as the first polymer. Using EPOCROS (registered trademark) WS-300, the first polymer was diluted with water so that the concentration of the first polymer became 5% by mass, thereby obtaining a first polymer solution.

[0227] [Preparation of the Second Polymer Solution]

[0228] [Synthesis Example 3-1]

[0229] 1.7 g of MAA, 20.0 g of MPC and 1.4 g of BMA were dissolved in a mixed solvent of 46.0 g of water and 46.0 g of ethanol to obtain a polymerization solution. After the temperature of the polymerization solution was raised to 55°C under a nitrogen atmosphere, 0.29 g of PB-ND was added to initiate polymerization. After 3 hours, the temperature was raised to 75°C and the mixture was further reacted for 2 hours to obtain a copolymer solution. After removing impurities from the obtained polymer solution by dialysis purification, the solution was diluted with water so that the concentration of the second polymer became 5% by mass to obtain a second polymer aqueous solution.

[0230] [Synthesis Examples 3-2 to 3-4]

[0231] Except that the amount of each component in the polymerization solution and the polymerization conditions were changed as shown in Table 2, a second polymer aqueous solution was obtained in the same manner as in Synthesis Example 3-1.

[0232] [evaluate]

[0233] [transparency]

[0234] The transparency of the hydrogels (before coating) and contact lenses (after coating) was visually evaluated.

[0235] [Water content]

[0236] The water content of hydrogels and contact lenses was measured according to the method described in ISO 18369-4.

[0237] [Elongation at break]

[0238] The elongation at break of the hydrogel and the contact lens was measured using a breaking strength analyzer of BAS-3305 (W) manufactured by YAMADEN co., ltd. according to JIS-K7127. A 2N load cell was used. As a measurement sample, a hydrogel or contact lens cut into a width of 2 mm was used, pulled at a rate of 1 mm / s with a clamping interval of 6 mm, and the elongation at break was evaluated according to the position where the sample broke.

[0239] [Oxygen permeability coefficient (Dk)]

[0240] The oxygen permeability of contact lenses was measured according to the method described in ISO 18369-4.

[0241] [WBUT: Water Breakdown Time]

[0242] For the WBUT of the hydrogel and the contact lens, the hydrogel and the contact lens were quietly taken out, and the time until the water film on the surface thereof was disconnected was measured with a stopwatch.

[0243] When the WBUT was 10 seconds or more, it was determined that the wettability was good.

[0244] [Lubricity]

[0245] For comparison, the lubricity of polymacon (a soft contact lens comprising 2-hydroxyethyl methacrylate (HEMA) as a main component) and omafilcon A (a soft contact lens comprising 2-hydroxyethyl methacrylate and 2-methacryloyloxyethyl phosphorylcholine as main components) on fingertips was evaluated by sensory evaluation.

[0246] The evaluation was performed on a 10-point scale, and when the surface lubricity of polymacon was 2 and the surface lubricity of omafilcon A was 8, the scores were as follows.

[0247] 1: Lowest lubricity.

[0248] 10: Highest lubricity.

[0249] When the score was 6 or more, the lubricity was determined to be good.

[0250] [Durability]

[0251] The contact lens was rinsed with saline solution, then placed with the inside of the lens facing up on the palm of the hand opposite to the dominant hand, and 1 mL of saline solution was dropped on it. The pad of the index finger of the dominant hand was brought into contact with the inside of the contact lens and gently pressed, moving the lens forward, backward, left and right, and rubbing 30 times for cleaning. After repeating the operation 14 times and 30 times, the lubricity and wettability were evaluated, respectively.

[0252] A: Wettability and lubricity are not reduced.

[0253] B: Wettability or lubricity is reduced.

[0254] C: Wettability and lubricity are reduced.

[0255] [Example 1]

[0256] Methafilcon A (contact lens made of a copolymer of HEMA and MAA) was used as the hydrogel. The hydrogel was immersed in the first polymer solution prepared in Synthesis Example 2-1 and heated at 75°C for 2 hours, thereby bonding the hydrogel and the first polymer to each other via a covalent bond and forming a first coating on the surface of the hydrogel.

[0257] Next, the hydrogel having the first coating layer was immersed in the second polymer solution prepared in Synthesis Example 3-1 and heated at 75° C. for 2 hours to obtain a contact lens in which the second polymer was covalently bonded to the first polymer and a hydrophilic coating layer was formed on the surface.

[0258] The obtained contact lenses were thoroughly washed with water, then immersed in a physiological saline solution adjusted according to ISO18369-3, and sterilized at 121° C. for 20 minutes, and various evaluations were performed.

[0259] [Examples 2 to 4]

[0260] A contact lens having a hydrophilic coating on the surface was obtained in the same manner as in Example 1 except that the hydrogel, the first polymer, and the second polymer were changed as shown in Table 3, and various evaluations were performed.

[0261] [Example 5]

[0262] The hydrogel of Synthesis Example 1-4 was used as the hydrogel. The hydrogel was immersed in the first polymer solution containing oxazoline groups and oleic acid bound to the oxazoline groups adjusted in Synthesis Example 2-3 at room temperature for 1 hour to form a first coating. Next, the hydrogel having the first coating was immersed in the second polymer solution adjusted in Synthesis Example 3-4 and heated at 75°C for 2 hours to obtain a contact lens in which the second polymer was bound to the first polymer via a covalent bond and a hydrophilic coating was formed on the surface.

[0263] The obtained contact lenses were thoroughly washed with water, then immersed in a physiological saline solution adjusted according to ISO18369-3, and sterilized under the conditions of 121° C. and 20 minutes, and various evaluations were performed.

[0264] [Comparative Example 1]

[0265] Polymacon (soft contact lens containing HEMA as a main component) was used as the hydrogel. The hydrogel was immersed in the first polymer solution (Synthesis Example 2-4) prepared using EPOCROS (registered trademark) WS-300 and heated at 75°C for 2 hours. In this case, the hydrogel and the first polymer did not form a bond.

[0266] Next, the hydrogel was immersed in the second polymer solution prepared in Synthesis Example 3-1 and heated at 75° C. for 2 hours.

[0267] The obtained contact lenses were thoroughly washed with water, then immersed in a physiological saline solution adjusted according to ISO18369-3, and sterilized under the conditions of 121° C. and 20 minutes, and various evaluations were performed.

[0268] [Comparative Example 2]

[0269] The hydrogel prepared in Synthesis Example 1-1 was used. The hydrogel was immersed in the first polymer solution prepared in Synthesis Example 2-2 and heated at 75° C. for 2 hours to obtain a contact lens in which the first polymer was bonded to the hydrogel via a covalent bond and only the first polymer was coated on the surface thereof.

[0270] The obtained contact lenses were thoroughly washed with water, then immersed in a physiological saline solution adjusted according to ISO18369-3, and sterilized under the conditions of 121° C. and 20 minutes, and various evaluations were performed.

[0271] [Comparative Example 3]

[0272] The hydrogel prepared in Synthesis Example 1-2 was used. The hydrogel was immersed in the second polymer solution prepared in Synthesis Example 3-2 and heated at 75° C. for 2 hours. In this case, the hydrogel and the second polymer did not form a bond.

[0273] The obtained contact lenses were thoroughly washed with water, then immersed in a physiological saline solution adjusted according to ISO18369-3, and sterilized under the conditions of 121° C. and 20 minutes, and various evaluations were performed.

[0274] The contact lenses of Examples 1 to 5 had no differences in transparency, water content, elongation at break, and Dk compared to the hydrogels before coating the first polymer and the second polymer.

[0275] Furthermore, unlike the hydrogel before coating the first polymer and the second polymer, the contact lenses of Examples 1 to 5 have good wettability and lubricity.

[0276] Furthermore, the contact lenses of Examples 1 to 5 had good durability.

[0277] That is, even when the contact lenses of Examples 1 to 5 are worn continuously for a long period of time, since the surfaces of the contact lenses have sufficient hydrophilicity and lubricity, the user can use the contact lenses for a long period of time without feeling discomfort.

[0278] In the contact lens of Comparative Example 1, since only the second polymer was bonded to the hydrogel and the first polymer was not bonded, the surface of the contact lens was not hydrophilized, and the wettability and lubricity of the contact lens after the treatment were poor.

[0279] In the contact lens of Comparative Example 2, only the first polymer is bonded to the hydrogel, and the wettability and lubricity of the contact lens after treatment are good, but since the lubricity decreases after washing the contact lens 14 times and the wettability also decreases after washing the contact lens 30 times, the durability of the coating is insufficient.

[0280] Since the contact lens of Comparative Example 3 was not coated with the first polymer, the hydrogel and the second polymer could not be combined, and the surface of the contact lens was not hydrophilized.

[0281] Therefore, the wettability and lubricity of the contact lenses treated with the coating are poor.

[0282] [Table 1]

[0283]

[0284] [Table 2]

[0285]

[0286] [Table 3]

[0287]

[0288] [Table 4]

[0289]

[0290] Industrial Applicability

[0291] An object of the present invention is to provide a soft contact lens whose surface has sufficient hydrophilicity and lubricity even when the soft contact lens is worn continuously for a long period of time.

[0292] Although the present invention has been described in detail and with reference to specific embodiments thereof, it will be apparent to one skilled in the art that various changes or modifications can be made to the present invention without departing from the spirit and scope of the present invention.

[0293] This application is based on the Japanese patent application filed on June 2, 2022 (Japanese Patent Application No. 2022-090441), the contents of which are incorporated herein by reference.

Claims

1. A soft contact lens, comprising the following (1), (2) and (3), or (1'), (2') and (3'): (1) a hydrogel (P1), wherein the hydrogel (P1) has a carboxyl group and / or a phenolic hydroxyl group, (2) a first coating layer having oxazoline groups formed on the surface of the hydrogel (P1), the first coating layer comprising a first polymer (P2), the first polymer (P2) comprising a constituent unit derived from a monomer containing an oxazoline group, and (3) a second coating layer, the second coating layer having carboxyl groups and / or phenolic hydroxyl groups formed on the surface of the first coating layer, the second coating layer comprising: A second polymer (P3), the second polymer (P3) comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate, and constituent units derived from carboxyl-containing monomers and / or constituent units derived from phenolic hydroxyl-containing monomers; or a second polymer (P3), the second polymer (P3) being polymerized in the presence of a chain transfer agent containing carboxyl and / or phenolic hydroxyl groups or an initiator containing carboxyl and / or phenolic hydroxyl groups and comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate, wherein: The carboxyl groups and / or phenolic hydroxyl groups of the hydrogel (P1) are bonded to the oxazoline groups of the first coating via covalent bonds, and the oxazoline groups of the first coating are bonded to the carboxyl groups and / or phenolic hydroxyl groups of the second coating via covalent bonds, or, (1') hydrogel (P1'), (2') a first coating layer having oxazoline groups formed on the surface of the hydrogel (P1') and fatty acids covalently bonded to the oxazoline groups, the first coating layer comprising a first polymer (P2'), the first polymer (P2') comprising a constituent unit derived from a monomer containing an oxazoline group and bonded to the fatty acid covalently bonded to the oxazoline group, and (3') a second coating layer, the second coating layer having carboxyl groups and / or phenolic hydroxyl groups formed on the surface of the first coating layer, the second coating layer comprising: a second polymer (P3), the second polymer (P3) comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate, and constituent units derived from carboxyl group-containing monomers and / or constituent units derived from phenolic hydroxyl group-containing monomers; or a second polymer (P3), the second polymer (P3) being polymerized in the presence of a chain transfer agent containing carboxyl groups and / or phenolic hydroxyl groups or an initiator containing carboxyl groups and / or phenolic hydroxyl groups and comprising constituent units derived from 2-(meth)acryloyloxyethyl phosphorylcholine, polyethylene glycol (meth)acrylate and / or methoxypolyethylene glycol methacrylate, wherein: The hydrogel (P1′) is bonded to the first coating layer by introducing fatty acids, and the oxazoline groups of the first coating layer are bonded to the carboxyl groups and / or phenolic hydroxyl groups of the second coating layer via covalent bonds.

2. The soft contact lens according to claim 1, wherein The hydrogel (P1) or (P1′) comprises: a constituent unit derived from (meth)acrylic acid or poly(meth)acrylic acid; and / or a constituent unit derived from hydroxyphenyl(meth)acrylate.

3. The soft contact lens according to claim 1, wherein The fatty acid is one or more selected from saturated fatty acids having 6 to 30 carbon atoms and unsaturated fatty acids having 6 to 30 carbon atoms.

4. The soft contact lens according to any one of claims 1 to 3, wherein: The first coating layer includes a first polymer (P2) or (P2′), wherein the first polymer (P2) or (P2′) includes a constituent unit derived from 2-isopropenyl-2-oxazoline.

5. The soft contact lens according to any one of claims 1 to 3, wherein: The second coating layer comprises a second polymer (P3) comprising a constituent unit derived from (meth)acrylic acid and / or a constituent unit derived from hydroxyphenyl (meth)acrylate.

6. The soft contact lens according to any one of claims 1 to 3, wherein: The second coating layer includes a second polymer (P3) comprising a constituent unit derived from 2-methacryloyloxyethyl phosphorylcholine.

7. A method for manufacturing the soft contact lens according to any one of claims 1 to 3, the method comprising the following steps: (1) a step of immersing the hydrogel (P1) having carboxyl groups and / or phenolic hydroxyl groups in a solution in which a first polymer (P2) having an oxazoline group is dissolved; and (2) A step of immersing the hydrogel having the first coating layer formed thereon after the immersion in step (1) in a solution in which a second polymer (P3) having a carboxyl group and / or a phenolic hydroxyl group is dissolved.

8. A method for manufacturing the soft contact lens according to any one of claims 1 to 3, the method comprising the following steps: (1) immersing the hydrogel (P1) in a solution in which a first polymer (P2′) is dissolved, wherein the first polymer (P2′) has an oxazoline group and a fatty acid covalently bonded to the oxazoline group; and (2) A step of immersing the hydrogel having the first coating layer formed thereon after the immersion in step (1) in a solution in which a second polymer (P3) having a carboxyl group and / or a phenolic hydroxyl group is dissolved.

Citation Information

Patent Citations

  • Mowing work machine

    JP2022090441A

  • Surface treatment of silicone medical devices

    WO2001074932A1